2014
DOI: 10.1179/2045772314y.0000000247
|View full text |Cite
|
Sign up to set email alerts
|

The application of implementation science for pressure ulcer prevention best practices in an inpatient spinal cord injury rehabilitation program

Abstract: Objectives: To implement pressure ulcer (PU) prevention best practices in spinal cord injury (SCI) rehabilitation using implementation science frameworks. Design: Quality improvement. Setting: SCI Rehabilitation Center. Participants: Inpatients admitted January 2012 to July 2013. Interventions: Implementation of two PU best practices were targeted: (1) completing a comprehensive PU risk assessment and individualized interprofessional PU prevention plan (PUPP); and (2) providing patient education for PU prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…43 Provision of prevention education has also been shown to reduce PI recurrence. 21 Other drivers 21,38 of tissue integrity such as PI risk assessment have previously been implemented through other initiatives 26 and are often required to be monitored organizationally. 20 We acknowledge that daily skin checks are a beneficial and necessary first step, but are not to sufficient to guarantee the absence of PIs, and that several other practices contribute to maintenance of tissue integrity in individuals with SCI/D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Provision of prevention education has also been shown to reduce PI recurrence. 21 Other drivers 21,38 of tissue integrity such as PI risk assessment have previously been implemented through other initiatives 26 and are often required to be monitored organizationally. 20 We acknowledge that daily skin checks are a beneficial and necessary first step, but are not to sufficient to guarantee the absence of PIs, and that several other practices contribute to maintenance of tissue integrity in individuals with SCI/D.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Priority areas include: prevention and effective management of PIs through best practice guidelines, 23 care pathways, and patient and caregiver resources. 4,24,25 PI risk factors after SCI/D include: increasing age, male, increasing time post-injury, motor complete injury, severity of muscle atrophy, presence of urinary or fecal incontinence, renal impairment, anemia, underweight, increased tissue temperature, 24 difficulties with level transfers 26 or deep tissue injury on ultrasound. 27,28 With greater focus on patient safety in healthcare settings, organizations like the Agency for Healthcare Research and Quality and the Institute for Healthcare Improvement have identified the need for quality indicators related to PI to measure the effectiveness of quality improvement interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Effectively repositioning patients at every 2 hours would require more manpower in a public health system stricken by chronic budget issues. Use of a prediction score such as the SCI Pressure Ulcer Scale (SCIPUS) could be beneficial for identifying patients with higher risk of PUs 17,18 and could result in better resource allocation. Pneumonia rates in our population were similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability and sensitivity have not been fully established for existing tools in persons with SCI [ 7 ] despite the unique characteristics of this population (eg, lack of sensation and muscle wasting) [ 3 ]. Salzberg and colleagues devised a risk assessment scale specific to the SCI population; although used in a few SCI/D Centers [ 8 ], the psychometrics of this tool are limited [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%